Health related behavioral changes during COVID-19 Movement Control Order (MCO) among medical students in institute of higher education Sabah, Malaysia Borneo: a qualitative study - Loganathan Salvaraji; Mohammad Saffree Jeffree; Ahmad Asyraf Abdul Rahim; Hemanath Sinnathamby; Mohd Fazeli Sazali; Nafsah Dulajis; Puteri Nureylia Amir; Haryati Abdul Karim; Fredie Robinson (Malaysian Public Health Physicians Association, 2022)
SARS-CoV-2 virus created a huge health impact due to isolation, quarantine, or lockdown. University students also affected with the closure of institute and switch in teaching methods. The objective of this study is to explore the health-related lifestyle changes among university students during the implementation of movement control order. Secondly, we aimed to convoke suggestions and recommendations to promote healthy living amidst university students. This study implemented qualitative method via using a semi-structured interview. Three focus group discussions were conducted consisting of 12 participants recruited from snowball sampling method. Utilizing verbatim transcription approach, an inductive thematic point was sketch for data analysis. Seven male and five female students with a mean age of 20 ± 1.3 years (range 19-23) were recruited into this study. Four themes identified from the interview. Physical health influence by administrative roles to physically inactive and less sport activity. Secondly, mental health concern towards mixed emotions, coping strategy, psychological adjustment, and mental health issues. Variation and self-prepare food, food supply, dietary habit and dietary pattern contribute to changes in food intake. Student lifestyles modulate to sleep hygiene, alcohol consumption, online classes problem, individual factors, and other unhealthy activities. Some students experience no difference in the surrounding transformation. During the pandemic, students experienced health related-behavioural changes involving physical health, mental health, dietary and lifestyle. Even though some informants perceived no changes in certain aspect, they still experience health-related behavioural changes in other aspect linked to health.